(untitled) (Semiárida, 2020)
The objective of this work was to evaluate the agronomical and phenological performance of several safflower cultivars (Carthamus tinctorius L.) in the Pampean Semiarid region. The trial was carried out al Anguil Agricultural Experiment Station, La Pampa, Argentina, during the period 2009/2010. The treatments were 14 commercial cultivars arranged in a design of random blocks with 3 repetitions. The experimental plots consisted of 4 furrows at distance of 0.52 m between them with a length of 5 m. Aconventional tillage was applied to the manual sowing 09/08/2009. The mechanized harvest took place on the 9 th of February this year. Results were analyzed by ANOVA and Duncan test al 5%. There were not important differences among cultivars concerning the occurrence of phenological stages recorded during the crop cycle. Considerable differences on the average yield of the 14 evaluated safflower cultivars were not found. However, a highly important difference in the percentage of oil content was detected. With reference to the crop development, it was observed that the plants neither achieved their maximum potential nor a good structure. Despite the fact previously mentioned, the yields can be considered satisfactory, as the crop completed its cycle.